39 Evidence that Haemodynamic Response to VV Delay Optimisation of Crt Devices May be Simply a Function of the Method of Programming AV Delay. (31st May 2014) - Afzal Sohaib, SM; Jones, Siana; Kyriacou, Andreas; Manisty, Charlotte; Mayet, Jamil; Kanagaratnam, Prapa; Peters, Nicholas; Hughes, Alun; Whinnett, Zachary; Francis, Darrel
Abstract : Background: The term "resynchronisation" indicates restoration of simultaneity, which by implication refers to ventricular timings (VV delay) rather than atrioventricular (AV) delay. However, while AV delay adjustment causes large haemodynamic effects, different laboratories have reported contradictory results concerning the strength of the effect of VV optimisation. Method and Results: 22 patients in sinus rhythm with existing CRT-P/D underwent VV optimisation using non-invasive systolic blood pressure. VV optimisation curves were constructed four ways: (a) atrium to left ventricle delay (A-LV) kept constant, (b) A-RV delay kept constant, (c) time to the first-activated ventricle kept constant, (d) time to the second-activated ventricle kept constant.In 11 patients this was performed with AV delay 120ms, and in 11 at AV-optimum. At AV 120ms, time to the first ventricular lead (left or right) was the overwhelming determinant of haemodynamics (13.75 mmHg at +/- 80ms, p < 0.001) with no significant effect of time to the second lead (0.47 mmHg, p = 0.50) p < 0.001 for the difference.At AV-optimum, time to first ventricular lead again had a larger effect (5.03 mmHg, p < 0.001) than time to second (2.92 mmHg, p = 0.001), p = 0.02 for the difference. Conclusion: Time to the first ventricular activation is the overwhelming determinant of circulatory function, regardless of whether this is the left or right ventricular lead.If this is kept constant, the effect of changing the time to the second ventricle is small or nil, and does not appear to be beneficial.In practice it may be advisable to focus on AV delay optimisation and leave VV delay at zero.